Ultra-sensitive H2 sensors based on flame-spray-made Pd-loaded SnO2 sensing films - Liewhiran C. (2014)
In this paper, ultra-sensitive hydrogen (H2) gas sensors based on flame-spray-made Pd-catalyzed SnO2 nanoparticles is presented. Pd-loaded SnO2 crystalline nanoparticles with high specific surface area and well-controlled size were synthesized by flame spray pyrolysis (FSP) in one step. The particle properties were characterized by XRD, BET, SEM, TEM and EDS analyses. The H2-sensing performances in terms of sensor response, response time and selectivity were optimized by varying Pd concentration between 0.2 and 2 wt%. An optimal Pd concentration for H2 sensing was found to be 0.2 wt%. The optimal sensing film (0.2 wt% Pd/SnO2, 10 μm in thickness) showed an ultra-high sensor response of ∼104 to 1 vol% of H2 at 200 °C and very short response time within a few seconds. Moreover, the optimum sensing temperature of Pd-loaded SnO2 films was shifted to a lower value compared with that of unloaded SnO2 film. The significant enhancement of H2 sensing performances was attributed to highly effective spillover mechanism of well-dispersed Pd catalyst in SnO2 matrix at low Pd-loading concentration. Furthermore, the catalyst selectivity of Pd toward H2 was found to be significantly higher than those of two other noble metals including Pt and Ru, respectively. Therefore, the flame-made 0.2 wt% Pd/SnO2 sensors is one of the most promising candidates for highly sensitive and selective detection of H2. © 2012 Elsevier B.V. All rights reserved.